IMPLEMENTASI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA DI SMK N 9 SEMARANG SEBAGAI SEKOLAH PUSAT KEUNGGULAN - Nanda Aji Setyaputri; Rana Sharjeel Akhtar; Muh. Adrikni Al Hakim; Nina Oktarina; Joko Widodo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the implementation strategy for the Strengthening Pancasila Student Profile Project at SMK N 9 Semarang as a center of excellence school. Using a descriptive qualitative approach, data collection was carried out through structured observation and interviews. Based on the research results, it is known that SMK N 9 Semarang has used the Independent Curriculum since 2021. One of the activities that must be carried out in implementing the Independent Curriculum is implementing the Pancasila Student Profile Strengthening Project (P5), and there is 1 (one) driving teacher at SMK N 9 Semarang. Implementation of P5 is carried out through several stages, including (1) forming a team of facilitators, (2) identifying the level of readiness of SMK N 9 Semarang, (3) Designing Dimensions, Themes, and Time Allocation for the Strengthening Pancasila Student Profile Project, (4) Preparing Project Modules (5) Reporting the Results of the Strengthening Pancasila Student Profile Project. The implementation of P5 at SMK N 9 Semarang has been running effectively. However, its implementation has several obstacles: limited school budgets, lack of human resources, and teachers' understanding of the modules at SMK N 9 Semarang.